Confirmatory validation of a brief patient-reported outcome measure assessing psychological distress in caregivers of malignant mesothelioma patients: the Mesothelioma Psychological Distress Tool–Caregivers - Granieri, Antonella; Franzoi, Isabella Giulia; Sauta, Maria Domenica; Marinaccio, Alessandro; Mensi, Carolina; Rugarli, Sabrina; Migliore, Enrica; Cozzi, Ilaria; Cavone, Domenica; Vimercati, Luigi; Grosso, Federica; Bertolotti, Marinella; et al. (Frontiers in Psychology, 2024)
Objective The diagnosis of malignant mesothelioma (MM) can be devastating for both patients and caregivers, who may experience intense suffering from a physical, psychological, and interpersonal perspective. Despite the extensive literature on caregiver distress, there is a lack of validated measures to provide evidence of psychological distress of caregivers of MM patients. Therefore, in a previous study we developed the Mesothelioma Psychological Distress Tool–Caregivers (MPDT-C) to evaluate the specific profile of psychological distress in this population. This paper describes the item selection, factor analysis, and psychometric evaluation of the revised MPDT-C. Methods The analyses of this work first aimed to confirm the previous factorial structure. In the case of nonfit, it aimed to find an alternative structure and causes of nonfit in the model. Examination of the fit of the factorial model was conducted using a Bayesian approach. Results The final version of the MPDT-C is a 7-item self-report questionnaire consisting of one factor (Burden for the caregiver). Conclusion Having a short self-report questionnaire to assess the psychological distress experienced by caregivers of MM patients has several advantages. First, it is suited to epidemiological studies where multiple variables and measures are involved. Second, it is easy to administer and does not take much time to complete. Therefore, the MPDT-C can also be administered in clinical contexts, perhaps when MM patients attend follow-up medical evaluation. Lastly, short measures are less affected by cognitive fatigue, which is very common in a long battery of tests and could affect response reliability.